A Case Report Disfonia et causa Nodul Vocal Cords Bilateral - Hadaina, Siti Jaisy Millah; Mutia, Dita; Nafatasya Ayu Rahmansyah; Latifa Intan Rahma; Haldy Dwi Febrian (Faculty of Medicine, Universitas Mataram, 2025)
Dysphonia is a commonly used term for any voice disorder resulting from abnormalities in the organs of phonation, especially the larynx, whether organic or functional. Vocal cord nodules or often known as “singer's nodes”, “screamer's nodes” or “teacher's nodes” are one of the most common causes of dysphonia in children. It is known that vocal cord nodules are a condition where there is swelling of the bilateral vocal cords of varying sizes, which can generally be found in the center of the vocal cord membrane. These nodules are characterized by epithelial thickening with different levels of inflammatory reaction in the superficial layer of the lamina propia. In this case report will discusses abouta 49-year-old woman who came to the ENT clinic of the NTB Provincial Hospital with a chief complaint of hoarseness. Furthermore, from the anamnesis, physical examination and supporting examination, the patient was diagnosed with dysphonia ec bilateral vocal cord nodules.